Antibiofilm Effect of Biogenic Silver Nanoparticles Combined with Oregano Derivatives against Carbapenem-Resistant Klebsiella pneumoniae - Sara Scandorieiro; Franciele Maira M. B. Teixeira; Mara C. L. Nogueira; Luciano A. Panagio; Admilton G. de Oliveira; Nelson Durán; Gerson Nakazato; Renata K. T. Kobayashi (MDPI AG, 2023)
Resistant bacteria may kill more people than COVID-19, so the development of new antibacterials is essential, especially against microbial biofilms that are reservoirs of resistant cells. Silver nanoparticles (bioAgNP), biogenically synthesized using Fusarium oxysporum, combined with oregano derivatives, present a strategic antibacterial mechanism and prevent the emergence of resistance against planktonic microorganisms. Antibiofilm activity of four binary combinations was tested against enteroaggregative Escherichia coli (EAEC) and Klebsiella pneumoniae carbapenemase-producing K. pneumoniae (KPC): oregano essential oil (OEO) plus bioAgNP, carvacrol (Car) plus bioAgNP, thymol (Thy) plus bioAgNP, and Car plus Thy. The antibiofilm effect was accessed using crystal violet, MTT, scanning electron microscopy, and Chromobacterium violaceum anti-quorum-sensing assays. All binary combinations acted against preformed biofilm and prevented its formation; they showed improved antibiofilm activity compared to antimicrobials individually by reducing sessile minimal inhibitory concentration up to 87.5% or further decreasing biofilm metabolic activity and total biomass. Thy plus bioAgNP extensively inhibited the growth of biofilm in polystyrene and glass surfaces, disrupted three-dimensional biofilm structure, and quorum-sensing inhibition may be involved in its antibiofilm activity. For the first time, it is shown that bioAgNP combined with oregano has antibiofilm effect against bacteria for which antimicrobials are urgently needed, such as KPC.